Protective Effect of Theaflavin on Erythrocytes Subjected to In Vitro Oxidative Stress - Mahejabeen Fatima; Rajesh Kumar Kesharwani; Krishna Misra; Syed Ibrahim Rizvi (Biochemistry Research International)
Antioxidant and free radical scavenging effect of black tea theaflavins has been shown in many epidemiological studies. In the present work we report the protective mechanism of tea theaflavins on biomarkers of oxidative stress, which are elevated during stress conditions. We hereby report the in vitro effect of theaflavins on erythrocyte malondialdehyde (MDA), intracellular reduced glutathione (GSH), and plasma membrane redox system (PMRS) of rats. The effect of theaflavin on PMRS has also been validated through an in silico docking simulation study using Molegro Virtual Docker (MVD). We report that theaflavins show significant protection to erythrocyte against oxidative stress induced by tert-butyl hydroperoxide (t-BHP). The findings suggest a possible protective role of theaflavins as antioxidant.